Absolute or relative stability in minimal invasive plate osteosynthesis of simple distal meta or diaphyseal tibia fractures?. Issue 6 (June 2017) - Wenger, R.; Oehme, F.; Winkler, J.; Perren, S.M.; Babst, R.; Beeres, F.J.P.
Abstract: Introduction: Minimal invasive plate osteosynthesis in simple distal meta or diaphyseal tibia fractures can be applied using absolute (lag screw and neutralisation plate; LSN) or relative stability (bridge plate; BP). The primary aim of the study was to compare time to radiological union and time to full weight bearing in the two groups (LSN vs. BP). Reduction was performed either percutaneously or by a minimally open approach (mini open). Secondary aim was to analyse the number of complications between both groups. Methods: Retrospective single centre review of patients with a simple distal meta or diaphyseal tibia fracture operated with a Locking Compression Plate (LCP) between 2009 and 2015 in a Level one Trauma Centre. Postoperative radiographs were assessed in a standardised manner. Time to radiological fracture union and time to full weight bearing were observed. Callus index and postoperative complications were analysed. Results: Fifty-seven patients with a minimum follow-up of 6 months were analysed. Forty-eight patients had a shaft (AO/OTA Type 42) and nine a distal tibia fracture (AO/OTA Type 43). Forty patients were treated with using the LSN concept and 17 patients with the BP concept. Median time to radiological fracture union was statistically significant shorter (p = 0.04) in the LSN group with 19 weeks compared to 27 weeks in the BP-group. Time to full weight bearing was 10 weeks in both groups. A total (including implant removal) of 35 reoperations were performed in the LSN-group and 18 in the BP-group. Wound healing disorders (deep surgical site infections) were seen less the LSN group in 3/40 (7.5%) compared to the BP-group with 3/17 (17.6%). In the LSN group, there was no statistical difference in time to union or weight bearing between a percutaneous or mini open approach. Conclusion: Stable osteosynthesis of simple distal meta or diaphyseal tibia fractures leads to faster radiologic fracture healing without an increase in complications or number of revisions compared to bridge plating. If a percutaneous reduction is not feasible for the insertion of a lag screw, a mini-open approach does not lead to a delay in fracture healing.